Prognostic value of simple measures of physical function and muscle strength in COPD: A systematic review. (January 2020) - Massierer, Daniela; Alsowayan, Waleed; Lima, Vanessa Pereira; Bourbeau, Jean; Janaudis-Ferreira, Tania
Abstract: Purpose: There has been an increased interest in simple measures of physical function and muscle strength that can be used in all clinical settings to assess individuals with chronic obstructive pulmonary disease (COPD) and predict their prognosis. The main objective was to examine the prognostic value of simple measures of physical function and muscle strength in relation to exacerbation, hospitalization and mortality in individuals with COPD. Methods: Medline, EMBASE, Cochrane and Web of Science were searched. We included prospective observational studies that examined the prognostic value of simple performed-based tests or self-reported measures of physical function or muscle strength in relation to exacerbation, hospitalization and mortality in individuals with COPD. Results: Seven articles met the inclusion criteria. The most commonly used tests were the handgrip strength (HGS) (n = 4) and 1-min sit-to-stand (STS) (n = 2). There were considerable variations in terms of characteristics of patients included, setting of recruitment, type of tests used, duration of follow-up and outcome measures of interest. The majority of the studies were classified as having "fair" or "poor" methodological quality. Conclusions: There is a limited number of studies examining the prognostic value of simple measures of physical function and muscle strength in relation to exacerbations, hospitalizations and mortality in individuals with COPD. To date, the HGS and 1-min STS tests are the most studied tests and seem to be suitable for prognosis purposes in individuals with COPD. However, more studies with better methodological quality are needed to confirm these findings. Highlights: Physical function tests may provide prognosis information in COPD patients. Few studies have studied the prognostic value of simple measures of physical function and muscle strength in relation to exacerbations, hospitalizations and mortality in individuals with COPD. The studies available are of low quality. More studies with better methodological quality are needed.